Historiography of science and technology in focus. A discussion with Professor Robert Fox - Robert Fox; Michał Kokowski (Studia Historiae Scientiarum)
The article is an extended discussion with a laureate of numerous international distinctions, Professor Robert Fox, about his career, intellectual fascinations, as well as changing methods, styles, approaches and themes in the historiography of science and technology.